Pengaruh Model Cooperative Learning Tipe Student Team Achievement Division (STAD) Terhadap Aktivitas dan Hasil Belajar IPA - Aryanto, Agus; Sucipto, Sucipto; Muhajir, Muhajir (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2021)
The purpose of this study was to examine the effect of the cooperative learning model of the Team Achievement Division (STAD) type on the activities and science learning outcomes of Class VIII students of SMP Negeri 2 Tanjungbumi. The quantitative approach was used with a quasi-experimental technique where the control group was not chosen at random. The instruments in this study were questionnaires, observation sheets, and tests. This study uses data analysis with the t-test formula. Based on the analysis of the data, it was concluded that there was an effect of the cooperative learning model of the Team Achievement Division (STAD) type on the activities and learning outcomes of Science Class VIII students of SMP Negeri 2 Tanjungbumi.